Poisoning substances taken by young people: a population-based cohort study - Tyrrell, Edward G.; Kendrick, Denise; Sayal, Kapil; Orton, Elizabeth (Royal College of General Practitioners, 2018)
Background: Globally, poisonings account for most medically-attended self-harm. Recent data on poisoning substances are lacking, but needed to inform self-harm prevention. Aim: To assess poisoning substance patterns and trends among 10-24 year olds across England from 1998-2014. Design and Setting: Open cohort study of 1,736,527 young people using linked Clinical Practice Research Datalink, Hospital Episode Statistics and Office for National Statistics mortality data. Method: Poisoning substances were identified by ICD-10 or Read codes. Incidence rates and adjusted incidence rate ratios (aIRR) were calculated for poisoning substances by age, sex, index of multiple deprivation and year. Results: 40,333 poisoning episodes were identified, with 58% specifying the substances involved. The most common substances were paracetamol (39.8%), alcohol (32.7%), NSAIDs (11.6%), antidepressants (10.2%) and opioids (7.6%). Poisoning rates were highest at ages 16-18 for females, 19-24 for males. Opioid poisonings increased 5-fold from 1998-2014 (females: aIRR 5.30, 95%CI 4.08-6.89; males: 5.11, 95%CI 3.37-7.76), antidepressant poisonings 3 to 4-fold (females: aIRR 3.91, 3.18-4.80, males: 2.70, 2.04-3.58), aspirin/NSAID poisonings 3-fold (females: aIRR 2.84, 2.40-3.36, males: 2.76, 2.05-3.72) and paracetamol poisonings 3-fold in females (aIRR 2.87, 2.58-3.20). Across all substances poisoning incidence was higher in more disadvantaged groups, with the strongest gradient for opioid poisonings among males (aIRR 3.46, 2.24-5.36). Conclusion: It is important that GPs raise awareness with families of the substances young people use to self-harm, especially the common use of over-the-counter medications. Quantities of medication prescribed to young people at risk of self-harm and their families should be limited, particularly analgesics and antidepressants.